Application of the Neoclassical Model to the Saudi Economy - Arabi, Khalafalla Ahmed Mohamed (Technium Business and Management, 2025)
This article uses real GDP growth statistics to investigate the determinants of real business cycles in the Saudi economy from 1970 to 2019. To find the origins of the business cycles, we used Stata 17 and the King and Rebelo model, which was published in 1999 and had six equations. We utilized Strata's "sbbq" module to detect the turning points. We computed the model parameters using Bayesian dynamic stochastic general equilibrium. The results revealed six turning points, divided into three peaks and three troughs. Furthermore, the findings show that our estimates nearly match those of King and Rebelo. According to theory, productivity shock is the most important element influencing behavior.